FAMILY READING AS A FACTOR OF SPIRITUAL AND MORAL DEVELOPMENT OF THE CHILD - Urazova M.B.; Babadzhanova T. B. (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the role of the library in the revival of traditions of family reading as an essential component in the spiritual and moral development of the child. Particular attention is paid to the forming of motherland image through family reading.